TANGGUNG JAWAB PEMEGANG SAHAM BANK SEBAGAI PERWUJUDAN PRINSIP KEHATI-HATIAN - NURWAHJUNI (2019)
The essential identification of shareholders is the owner of capital in a limited liability company. The law gives limited responsibility to shareholders characteristic. However, in practice, especially in banking business, limited liability is used to eliminate possibility of losses experienced by the shareholders, which in fact results in bank’s adversity and stakeholder of the banks, specifically the depositors. From the tables that are displayed, there are problems faced by the bank as a result of the actions of the shareholders of the banks concerned. There are two legal issues in research. First, the nature of the position of bank shareholders. Second, the responsibility of the bank's shareholders. In answering the two legal issues normative juridical method is used, by analyzing primary and secondary legal materials obtained by means of literature studies. In this study new arguments were found. The liability of bank shareholders comes out of the concept of liability based on BW. Without intentions, negligence and also on matters that are borne, bank shareholders are liable. The liability of shareholders is also comes from the concept of liability based on the Limited Liability Company Law. Limited shareholders rule do not apply to bank shareholders. Likewise with unlimited liability, without fault as Piercing The Corporate Veil based, bank shareholders are liable